Blue space as caring space – water and the cultivation of care in social and environmental practice. (12th October 2020) - Buser, Michael; Payne, Tom; Edizel, Özlem; Dudley, Lyze
ABSTRACT: This paper studies three sites or 'landscapes of care' in Leeds, Bristol and London where water and associated built and natural environments are used to co-construct and facilitate forms of social and environmental care. Our research narrates the ways in which blue spaces are cultivated for the production of particular forms of caring bodies and sensibilities. Interpreting care as both a doing (caring for) and emotion (caring about), we draw attention to the diverse practices and distributed nature of care in these environments. Our paper has three main insights. First, we draw attention to the role of water as both a material and site of care. Second, we identify a range of more-than-human benefits associated with blue spaces and how these emerge via collaborative, non-linear and reciprocal forms of care. Third, we argue that by understanding how care works in everyday social practice, new forms of ecological care and pro-environmental ways of living with the world can emerge.